2021
DOI: 10.51386/25815946/ijsms-v4i4p132
|View full text |Cite
|
Sign up to set email alerts
|

EFL Teachers’ Perceptions of Information Gap Activities in Teaching Speaking and Their Reflections on the Use of These Activities in Their Classrooms

Abstract: In teaching speaking, information gap activities are viewed as a useful tool which provides many advantages in teaching speaking language owning to the benefits it offers. Information gap activities give learners real motivation to communicate as they have opportunities to practice in actual situations. They give learners the chance to exchange information through communication. This research aims to investigate EFL teachers’ perceptions of information gap activities (IGAs) in teaching speaking English and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Perceptions about a particular strategy or method is also a key topic in second language research since the human side must be considered in order to determine the effectiveness of strategies or methods. In the available literature, it has been found that participant students and teachers held both positive and negative opinions about information gap activities to build speaking skills (Defrioka, 2016;Amalia, 2019;Humaera, Jumiati, & Safei, 2022;Ismaili & Bajrami, 2016;Namaziandost, Hashemifardnia, & Shafiee, 2019;Ortiz, 2019;Duyen, 2021). One of the most prevalent opinions by the participants was that IGAs enabled them to communicate in real contexts, which gave them a sense of purpose and desire to use the language (Duyen, 2021;Amalia, 2019).…”
Section: Students' Opinions Towards Information Gap Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceptions about a particular strategy or method is also a key topic in second language research since the human side must be considered in order to determine the effectiveness of strategies or methods. In the available literature, it has been found that participant students and teachers held both positive and negative opinions about information gap activities to build speaking skills (Defrioka, 2016;Amalia, 2019;Humaera, Jumiati, & Safei, 2022;Ismaili & Bajrami, 2016;Namaziandost, Hashemifardnia, & Shafiee, 2019;Ortiz, 2019;Duyen, 2021). One of the most prevalent opinions by the participants was that IGAs enabled them to communicate in real contexts, which gave them a sense of purpose and desire to use the language (Duyen, 2021;Amalia, 2019).…”
Section: Students' Opinions Towards Information Gap Activitiesmentioning
confidence: 99%
“…In the available literature, it has been found that participant students and teachers held both positive and negative opinions about information gap activities to build speaking skills (Defrioka, 2016;Amalia, 2019;Humaera, Jumiati, & Safei, 2022;Ismaili & Bajrami, 2016;Namaziandost, Hashemifardnia, & Shafiee, 2019;Ortiz, 2019;Duyen, 2021). One of the most prevalent opinions by the participants was that IGAs enabled them to communicate in real contexts, which gave them a sense of purpose and desire to use the language (Duyen, 2021;Amalia, 2019). Another aspect that they enjoyed and viewed as positive was pair work because of the friendly atmosphere that was created through which they felt less anxious and more willing to produce speech using the target language.…”
Section: Students' Opinions Towards Information Gap Activitiesmentioning
confidence: 99%